Derive this identity from the sum and difference formulas for cosine:

sin a sin b = (1 / 2)[cos(a – b) – cos(a + b)]

**Start with the right-hand side since it is more complex.**

**Please provide a reason with each step**

### 2 Answers | Add Yours

We use the formula for sum and difference of two angles for cosine.

`cos(a - b) = cosacosb + sinasinb`

`cos(a + b) = cosacosb - sinasinb`

So, we will have:

`1/2[cosacosb + sinasinb - (cosacosb - sinasinb)] = 1/2[cosacosb + sinasinb - cosacosb + sinasinb]`

Combine like terms.

`1/2[2sinasinb]`

Multiply.

`1/2[2sinasinb] = sinasinb`

Hence, right hand side is equal to left hand side.

Prostapheresis formula shows that:

`cos(a-b)-cos(a+b)=-2sin((a-b+a+b)/2)sin(((a-b)-(a+b))/2)`

`=-2sin a sin(-b)=2sina sin b`

`thus:`

`1/2(cos(a-b)-cos(a+b))=sin a sin b`

``

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes